Assessment and Analysis of Locating Housing and its Impact on Development Patterns in Damghan - Arjmand, Ahmad; Ali Khakpoor, Barat (International Journal of Engineering and Technology, 2018)
Understanding and management of urban street space capable of lighting it creates Urbanization process can be observed today in all countries this process, if it is considered natural and less worrisome, but if unplanned, the impaired and the ultimate goal is the welfare of citizens is not. Today, one of the problems of our cities and urban poor urban adverse effects that urban planning is a serious subjects. The aim of this study was to investigate locating housing and its effects onâ€ the development directions of Damghan. The research method based on purpose and on the basis of a descriptive nature that is the case in this study, the analytical hierarchy process (AHP) and Microsoft Excel and SPSS statistical analysis is used to produce tables.Â